Public debt in Mexico: dynamics and policy implications - Martínez Chapa, Oshiel; Salazar Castillo , Jorge Eduardo; Quispe Aruquipa, Saul Roberto (Political Questions, 2021)
The purpose of this paper is to analyze the factors that have driven the public debt in Mexico and its consequences on the economy. The hypothesis proposed is that the increase in debt is related to factors such as discretion in the management of public resources, the guarantee of oil resources, the cost of financial bailouts and the growing social spending exercised. The research question is: How has public debt evolved in the medium and long term, and what are the consequences? The methodology used is qualitative in that it analyzes the facts and documents, and the second is quantitative in that it uses a regression model in which a growth rate of the variable in question is used. The data come from institutions such as the Bank of Mexico, the World Bank, the Ministry of Finance and Public Credit (SHCP), as well as World Population Review. The paper concludes by highlighting the need for governments to adopt responsible policies in order to influence growth and economic development, and not that austerity policies cause low investment and unemployment in the country.